The future of the international oil market - Deagle, Edwin A.; Group of Thirty (New York : Group of Thirty, 1983)
This report examines relationship and its consequences among economy of the world. Furthermore it explores what might be done to improve the functioning of the oil market and its interaction.
Includes bibliographical footnotes.
osa 23/01/2019
Loans
Keywords: Petroleum industry and trade; Twentieth century